The devil in history : communism, fascism, and some lessons of the twentieth century - Tismaneanu, Vladimir (University of California Press, 2012)
The Devil in History is a provocative analysis of the relationship between communism and fascism. Reflecting the author's personal experiences within communist totalitarianism, this is a book about political passions, radicalism, utopian ideals, and their catastrophic consequences in the twentieth century's experiments in social engineering. Vladimir Tismaneanu brilliantly compares communism and fascism as competing, sometimes overlapping, and occasionally strikingly similar systems of political totalitarianism. He examines the inherent ideological appeal of these radical, revolutionary politi.